Injury of the cingulum in patients with putaminal hemorrhage: a diffusion tensor tractography study - Kwon, Hyeok Gyu; Choi, Byung Yeon; Kim, Seong Ho; Chang, Chul Hoon; Jung, Young Jin; Lee, Han Do; Jang, Sung Ho (Frontiers in Human Neuroscience, 2014)
Objectives: Little is known about the pathophysiological mechanisms of cognitive impairment in patients with putaminal hemorrhage(PH). Using diffusion tensor tractography(DTT), we investigated injury of the cingulum in patients with PH. Methods: We recruited 63 patients with PH, who were classified according to three groups, based on integrity of the cingulum to the lower portion of the genu of the corpus callosum: group A; preserved integrity, group B; discontinuation of integrity in the affected hemisphere, and group C; discontinuation of integrity in both hemispheres. Results: Thirty four patients(54.0%) belonged to group A, 16 patients(25.4%) to group B, and the remaining 13 patients(20.6%) to group C. Regarding the Mini-Mental State Examination, significant differences were observed between group A and group C, and between group B and group C without significant difference between group A and group B(p<0.05). In terms of the volume of hematoma, significant differences were observed among the three groups(p<0.05). Regarding the most anterior point of the hematoma, significant differences were observed between group A and groups B and C(p<0.05); in contrast, regarding the most point of hematoma, significant differences were observed between group C and groups A and B, respectively(p<0.05). Conclusions: We found that the anterior cingulum is vulnerable to PH. Therefore, our results suggest the necessity for evaluation of the cingulum in patients with PH particularly if the hematoma is large or close to the anterior margin or midline of the brain.